Sustainability and functional assessment of a mixed building technology solution - Bragança, L. (2004)
Most of the new construction solutions arise from the feeling that something should be done in order to answer current society concerns: reduction of energy consumption, minimization of pollution, etc. The aim of this paper is to evaluate the potentialities of a MBT – “Mixed Building Technology” solution. This solution was evaluated under the thermal, acoustic and natural lightning performance, and economical/environmental analysis.